1996
DOI: 10.1046/j.1365-2362.1996.109261.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant human erythropoietin in combination with parenteral iron in the treatment of postpartum anaemia

Abstract: Abstract. The authors compared the effect of recombinant human erythropoietin (rhEPO) in combination with iron with that of iron therapy only in the treatment of postpartum anaemia. Ninety patients (30 patients/ group) received either rhEPO (300 U kg ÿ 1 , i.v. or s.c., once) and iron (parenteral and oral), or iron therapy only. Erythropoiesis was assessed by haemoglobin and haematocrit increase, absolute reticulocyte counting and reticulocyte flow cytometry. Ferrokinetics was assessed by serum ferritin, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 36 publications
1
32
0
7
Order By: Relevance
“…No adverse effects were observed during the study. Similar conclusions were drawn by Breyman et al: rHuEpo 300 U/kg + IV iron 100 mg once followed by oral iron significantly increased Hb but no correction of ferritin levels was observed after two weeks of treatment 22 . Anemia due to heavy bleeding during delivery should be corrected without delay.…”
Section: Experience To Date With IV Iron Administration In the Perisusupporting
confidence: 87%
“…No adverse effects were observed during the study. Similar conclusions were drawn by Breyman et al: rHuEpo 300 U/kg + IV iron 100 mg once followed by oral iron significantly increased Hb but no correction of ferritin levels was observed after two weeks of treatment 22 . Anemia due to heavy bleeding during delivery should be corrected without delay.…”
Section: Experience To Date With IV Iron Administration In the Perisusupporting
confidence: 87%
“…Iron sucrose alone or in combination with recombinant human erythropoietin (rhEPO) has been successfully used in the treatment of anemia in pregnancy [5][6][7][8] as well as in the puerperium [9,10] .…”
mentioning
confidence: 99%
“…Moreover, adequate iron stores is an important prerequisite for a successful rHuEPO treatment [21]. Seven out of 26 patients (27%) of this study showed little or no response to rHuEPO combined with parenteral iron therapy.…”
Section: Discussionmentioning
confidence: 68%
“…rHuEPO has been tested as potential therapy in various maternal disorders during pregnancy. These include: end-stage renal disease [19], antepartum iron deficiency anemia [20], postpartum anemia [9,21], as well as anemia of pregnant women with chronic hematological disorders [13,14], and various more rare clinical conditions [11][12]. These studies showed that rHuEPO administration might be used to treat certain pregnancy anemias by stimulating maternal erythropoiesis or as an alternative for patients refusing blood transfusion.…”
Section: Discussionmentioning
confidence: 99%